New biochemical predictor of the ventricular tachyarrhythmias in patients with ischemic cardiomyopathy. (24th May 2021) - Atabekov, T; Batalov, R; Sazonova, S; Gusakova, S; Krivolapov, S; Khlynin, M; Popov, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction. The cardioverter-defibrillator (ICD) implantation is the most effective method for the sudden cardiac death (SCD) prevention. However, about 25% patients did not receive an ICD therapy during the first 5-years follow-up. At the same time ICD does not register ventricular tachyarrhythmias (VTA) events in patients with ICD implanted for the primary prevention of SCD. So, it's necessary to find out new prognostic markers of the VTA incidence, which will help to optimize the selection of patients who really need an ICD implantation. Currently, ST-2 and galectin-3 are actively studied in patients with coronary artery disease (CAD) and chronic heart failure due to their high potential prognostic value. Moreover, their role in the development of life-threatening arrhythmias is still poorly understood. In this regard, the study of the level of biomarkers of inflammation and myocardial fibrosis is relevant. Aim. To evaluate the prognostic value of the ST-2 and galectin-3 in VTA predicting in patients with coronary artery disease and left ventricular ejection fraction less than 35 %. Material and methods. The study included 40 patients (males – 36, median age – 64, 5 [57, 5; 68, 5] years) with CAD, II and III functional class of chronic heart failure, left ventricle ejection fraction less than 35 % and ICD implantation indications (primary prevention of the SCD). ST-2 and galectin-3 blood concentration were determined before ICD implantation. All patients were followed-up during 18 months. There were assessed arrhythmological events recorded in ICD memory and ICD-lead parameters. Results. The 1st group consisted of 10 (25, 0 %) patients with VTA events terminated with ICD antitachycardia pacing or shock, the 2nd group – 30 (75, 0 %) patients without VTA events. The univariate ROC-analysis showed that the high values of the ST-2 (p = 0, 003) and galectin-3 (p = 0, 045) were associated with frequent VTA events. Kaplan-Meier analysis showed that the ST-2 > 22, 48 ng/ml (p = 0, 02) and galectin-3 > 10, 95 ng/ml (p = 0, 009) significantly increase the risk of the VTA events. The multivariate ROC-analysis showed that only ST-2 increase (OR = 1, 1053; CI 95 %: 1, 0134-1, 2056; р = 0, 023) leaded to frequent VTA events. Conclusion. An increase of ST-2 more than 22, 48 ng/ml and galectin-3 more than 10, 95 ng/ml has predictive value in VTA assessing risk in patients with ischemic cardiomyopathy. In multivariate analysis, an independent predictor of VTA is the ST-2 increase more than 22, 48 ng/ml.